The viral protein gp120 decreases the acetylation of neuronal tubulin: potential mechanism of neurotoxicity - Avdoshina, Valeria; Caragher, Seamus P.; Wenzel, Erin D.; Taraballi, Francesca; Mocchetti, Italo; Harry, Gaylia Jean (Journal of neurochemistry, 2017)
The human immunodeficiency virus (HIV) envelope protein gp120 promotes axonal damage and neurite pruning, similar to that observed in HIV‐positive subjects with neurocognitive disorders. Thus, gp120 has been used to examine molecular and cellular pathways underlying HIV‐mediated neuronal dysfunction. Gp120 binds to tubulin beta III, a component of neuronal microtubules. Microtubule function, which modulates the homeostasis of neurons, is regulated by polymerization and post‐translational modifications. Based on these considerations, we tested the hypothesis that gp120 induces dynamic instability of neuronal microtubules. We first observed that gp120 prevents the normal polymerization of tubulin in vitro. We then tested whether gp120 alters the post‐translational modifications in tubulin by examining the ability of gp120 to change the levels of acetylated tubulin in primary rat neuronal cultures. Gp120 elicited a time‐dependent decrease in tubulin acetylation that was reversed by Helix‐A peptide, a compound that competitively displaces the binding of gp120 to neuronal microtubules. To determine whether post‐translational modifications in tubulin also occur in vivo, we measured acetylated tubulin in the cerebral cortex of HIV transgenic rats (HIV‐tg). We observed a decrease in tubulin acetylation in 5‐ and 9‐month‐old HIV‐tg rats when compared to age‐matched wild type. Neither changes in microglia morphology nor alterations in mRNA levels for interleukin‐1β and tumor necrosis factor α were detected in 5‐month‐old animals. Our findings propose neuronal microtubule instability as a novel mechanism of HIV neurotoxicity, without evidence of enhanced inflammation. In this study we show that HIV viral protein gp120 prevents the normal polymerization of tubulin. We demonstrated that gp120 decreases the levels of acetylated tubulin in primary rat neuronal cultures in a time‐dependent manner and that was reversed by a small peptide that displaces the binding of gp120 to neuronal microtubules. We also observed a decrease in tubulin acetylation in HIV‐tg rats. We propose neuronal microtubule instability as a novel mechanism of HIV neurotoxicity, without evidence of inflammation.